BACTERIOLOGICAL EVALUATION OF KWATA ABATTOIR WASTE WATER AWKA, NIGERIA - CM, EZEOKOLI; KC, AGU; JC, NWOSU; MU, ORJI; LI, UWANTA; ND, UMEODUAGU; AT, VICTOR-ADULOJU; BO, IKENWA (Innovare Journal of Sciences, 2023)
Abattoir wastes can have a detrimental effect on the environment, public health, animal health, and economy of a country if they are not effectively managed and controlled. The bacteriological evaluation of waste water from Kwata abattoir was carried out to determine the bacterial load present and if the waste water generated is suitable for direct discharge into the environment. A total of two samples were aseptically collected, in which the physicochemical analysis of the waste water showed objectionable color and odor, pH of 7.3 and 6.5, and temperature of 30.2°C and 25.3°C for samples A and B, respectively, of which the pH and temperature were within acceptable limits by WHO. The membrane filter method was used to determine the total coliform and thermotolerant coliform counts present per 100 mL of the samples using MacConkey agar and Eosin Methylene Blue Agar, respectively. The total viable count was obtained for both samples: 5.1×105 CFU/mL for sample A and 1.4×106 CFU/mL for sample B. Phenotypic and biochemical tests were carried out for four isolates, which include Escherichia coli, Salmonella spp., Bacillus spp., and Bacillus cereus. Thus, it can be concluded from the above study that untreated abattoir waste water contains a high level of pollutants, which supports the growth of the microbial population, as evidenced in the microbial study. Therefore, waste water has to be treated before discharge into the environment to protect public health and promote the safety of the environment.